PENGARUH STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN DI CV. WERRY GROUP - Feberlina Tafonao; Emanuel Zebua; Perlindungan F. Hulu; Sophia Molinda Kakisina (Jurnal Publikasi Manajemen Informatika, 2025)
This study aims to analyze the influence of marketing strategies on increasing sales, particularly for the "Sabun Cantik" product at CV. Werry Group in Gunungsitoli City. In the midst of rapid technological development and intense market competition, effective marketing strategies are essential for attracting and retaining customers. CV. Werry Group is a company engaged in various business sectors; however, it faces challenges in promoting one of its products, "Sabun Cantik." This product is not widely known by the public due to the suboptimal use of social media as a promotional tool and the lack of engaging and relevant marketing content. This research uses a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The results indicate that appropriate and innovative marketing strategies, particularly through social media, have a significant impact on increasing sales. Therefore, modern and adaptive marketing management is necessary to enhance product competitiveness and sales volume at CV. Werry Group in the future.